(untitled) (Journal of Economic Research & Business Administration, 2022)
In the article, the authors substantiate the relevance of studying consumer behavior. The purpose of the study is to identify the possibility of using analytical tools to identify the main factors, which influencing consumer behavior and being a priority to make a purchase decision. The survey method of primary research was chosen among 408 respondents to study this problem. This method was found on the basis of a sample survey called “snowball” method. The method of factorial estimation was used for data analysis. All data were analyzed in IBM SPSS 22 software. The authors describe in details the methodology of this study, with the provision of statistical analysis results. The method of factor analysis made it possible to identify five main factors influencing consumer behavior when they buy car batteries: “basic characteristics of batteries”, “marketing communications”, “sources of information”, “motivation” and “social factors”. The data obtained in the course of the survey allowed us to conclude that consumer behavior in the car battery market is determined by a combination of various variables within factors. The received results also made it possible to draw a conclusion about the completeness of the identified factors of consumer behavior and the need for further research in the context of studying the declared problem. Key words: consumer behavior, factor analysis, purchase decision-making, car batteries.